Prevalence of vitamin D deficiency and modifiable risk factors in patients with Crohn's disease: A prospective observational study. (24th October 2022) - Fletcher, Jane; Brown, Michaela; Hewison, Martin; Swift, Amelia; Cooper, Sheldon C.
Abstract: Aims: To determine the prevalence of vitamin D deficiency in adults with Crohn's Disease (CD) in Birmingham, UK (latitude 52.4°N, −1.9°E) and identify modifiable risk factors. Design/Method: A nurse‐led, single‐centre, prospective study was conducted over 5 months in 2019 and 2020 in outpatients with CD, at a tertiary referral hospital in Birmingham UK. Vitamin D (25OHD) levels were measured at a single timepoint by a dried blood spot sample. Modifiable risk factor data were collected including intake of vitamin D‐containing foods, use of vitamin D supplements, sun exposure and current smoking. Results: Total 150 participants (53.3% male, 79.3% white British). Vitamin D deficiency (25OHD <50 nmol/L) was found in 53.3%. 32.7% of participants took over‐the‐counter vitamin D supplements and 20.7% used prescribed supplements. We found that diets were generally poor in relation to vitamin D‐rich foods. In terms of sun exposure, few (18%) had visited a sunny country recently, and few (6%) covered their whole body with clothing. Most used High Sun Protection Factor (80%) with a median grade of SPF 45. Conclusion: Patients with CD are at high risk of vitamin D deficiency as defined by 25OHD < 50 nmol/L, with the prevalence of deficiency being highest during the winter months. Patients with CD in the UK are unlikely to maintain vitamin D levels from sunlight exposure, dietary sources or over‐the‐counter supplements. Impact: Patients with Crohn's Disease are at high risk of developing vitamin D deficiency but there is little data from the UK at this latitude. We demonstrate the prevalence and severity of vitamin D deficiency in people with Crohn's Disease in the UK. The prevalence of vitamin D deficiency in this group is high and warrants monitoring by nurses and clinical teams. Nurses and clinical teams should consider strategies for vitamin D supplementation in patients with Crohn's Disease.